2021
DOI: 10.1128/aac.01156-21
|View full text |Cite
|
Sign up to set email alerts
|

Epetraborole Is Active against Mycobacterium abscessus

Abstract: Benzoxaboroles are a new class of leucyl-tRNA synthetase inhibitors. We recently reported that the antitubercular 4-halogenated benzoxaboroles are active against Mycobacterium abscessus . Here, we find that the non-halogenated benzoxaborole epetraborole, a clinical candidate developed for Gram negative infections, is also active against M. abscessus in vitro and in a mouse model of infection. This expands the repertoire of advanced lead compounds for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…Our data and two recent publications [43,44] confirmed the activity of benzoxaboroles against mycobacteria using zebrafish and murine models of infection and we showed that benzoxaboroles can be potentiated when combined with norvaline. Specifically, we demonstrated that the combination of EPT with norvaline reduces the emergence of M. abscessus and M. tuberculosis mutants and results in increased activity in vivo compared to EPT.…”
Section: Discussionsupporting
confidence: 86%
“…Our data and two recent publications [43,44] confirmed the activity of benzoxaboroles against mycobacteria using zebrafish and murine models of infection and we showed that benzoxaboroles can be potentiated when combined with norvaline. Specifically, we demonstrated that the combination of EPT with norvaline reduces the emergence of M. abscessus and M. tuberculosis mutants and results in increased activity in vivo compared to EPT.…”
Section: Discussionsupporting
confidence: 86%
“…Sequencing leuS suggested that all resistant isolates had a single missense mutation in the leuS editing domain (residues 292 to 502), consistent with the mechanism of leucyl-tRNA synthetase inhibition. The S303L, V417M, and T322I residues were mutated in benzoxaborole-resistant M. abscessus mutants that were previously reported ( 18 , 19 ). Four other LeuRS missense mutations in the editing domain (i.e., D436E, L418P, Y421H, and D436N) were novel.…”
Section: Resultsmentioning
confidence: 99%
“…Despite M. abscessus resistance to most approved anti-TB drugs, we found that compound collections of TB actives provide a good source for hit identification (6). Screening series of advanced TB actives against M. abscessus identified several compounds with in vivo activity, including inhibitors of RNA polymerase (7), ATP synthase (8), Leucyl-tRNA synthetase (9, 10), DNA gyrase (11) and DNA clamp DnaN (12). Expanding on this strategy, we asked whether the recently identified novel class of tricyclic pyrrolopyrimidines (TPPs (13)), targeting DNA gyrase in Mycobacterium tuberculosis and various other bacteria (14, 15) is active against M. abscessus .…”
Section: Main Textmentioning
confidence: 99%
“…synthetase (9,10), DNA gyrase (11) and DNA clamp DnaN (12). Expanding on this strategy, we asked whether the recently identified novel class of tricyclic pyrrolopyrimidines (TPPs (13)), targeting DNA gyrase in Mycobacterium tuberculosis and various other bacteria (14,15) is active against M. abscessus.…”
mentioning
confidence: 99%